TEACHING AND LEARNING BUSINESS ENGLISH IN A GLOBALIZED WORLD - SIMION MINODORA OTILIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2014)
Globalization is the process of integration across world-space among the people, companies and governments of different nations, the term itself being increasingly used since the 1980s and especially 1990s.This process has been triggered by international trade and investment and aided by information technology and it has had a great impact on environment, culture, economic development and political systems all over the world. Globalization and the status of English as a world language have a great impact upon the teaching and learning of English worldwide. There is a growing interest in many countries in improving the quality of teaching English and many national education policies are adopted in order to increase the students’communication competence rather just having some knowledge about the language which was common in the past.